«Health schools» as the key factor of efficient cardiovascular disease prevention - N. V. Ekkert; V. V. Mikhaylovski (Сеченовский вестник)
In the Russian Federation, cardiovascular  diseases (CVD) accounts for about 57% of adult mortality. The aim of the study was to evaluate the CVD prevention eﬀectiveness in the patients attending «Schools of Health» at Health Centers in Tula and the Tula region. The study analyzed the major risk factors in arterial hypertension (AH) patients in «Schools of Health» in 2014. The study ﬁndings suggest that the priority AH risk factors were increased body mass index, elevated total cholesterol level and low physical activity. The study demonstrated that education programs fo AH patients at «Schools of Health» in Tula and the Tula region can not only inform the raise public awareness about the disease, the AH key risk factors, a modern drug and non-drug AH therapy, but also improve patients' quality of life, prevent AH progression and reduce the risk of serious complications  (e.g., stroke, myocardial infarction, etc.) which may result in disability and mortality in patients.